2010
DOI: 10.1179/146701010x12671178390717
|View full text |Cite
|
Sign up to set email alerts
|

Education and Rehabilitation of Deaf Children with Cochlear Implants: A Multidisciplinary Task

Abstract: In the last decade the population of deaf children has changed dramatically in a lot of countries, especially in those where universal neonatal hearing screening, early multi-disciplinary support, digital hearing aids and cochlear implants are available. Most of these children can acquire intelligible spoken language and choose spoken language as their main means of communication and for access to education, because they go to mainstream schools in larger proportions, and fewer to schools for the deaf. Mainstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
8
1
1
Order By: Relevance
“…Reliant Resilient Deaf education 38 52 10 Hard-of-hearing education 27 18 55 Mainstream education 19 15 65 Total group 28 29 43 Dutch Norm data [10][11][12][13][14][15] A logical assumption is that in deaf education also children with additional language difficulties should be present. Bilingual approaches (learning two languages) may not be best option for these children.…”
Section: Vulnerablementioning
confidence: 99%
See 1 more Smart Citation
“…Reliant Resilient Deaf education 38 52 10 Hard-of-hearing education 27 18 55 Mainstream education 19 15 65 Total group 28 29 43 Dutch Norm data [10][11][12][13][14][15] A logical assumption is that in deaf education also children with additional language difficulties should be present. Bilingual approaches (learning two languages) may not be best option for these children.…”
Section: Vulnerablementioning
confidence: 99%
“…As a result of both enhanced audition and vocabulary, improved reading comprehension and educational achievements were reported [11][12][13][14]. A number of studies reported that children with CI were able to attend mainstream education [15,16].…”
Section: Introductionmentioning
confidence: 95%
“…It takes into consideration the sequence of auditory listening skills to be trained (dimension 1, the levels of perception); the variety of materials to be used (dimension 2, the practice material and prosody) and the range of listening environments (dimension 3, the practice conditions). It also alerts the therapists to increase their expectations and to allow improved perception of soft sounds and speech; improved speech understanding in background noise, as well as localization of sound and speech ( 21 ). While planning auditory training exercises, therapists can simply select combinations of items from these three different dimensions of the Listening Cube.…”
Section: Methodsmentioning
confidence: 99%
“…The author focused on the skills required by the teachers and staff, including flexibility, technology orientation and updates, and ongoing professional development to cover the learning and emotional needs of the children, providing an appropriate environment for their psycho-social needs. As the author explained, the challenge for the near future is to be able to address the needs of each child, and deliver services depending on their abilities, expectations, and attitudes [8]. Although the advantages of technological sensory aids are definitively clear, it is still necessary to consider the special needs of the population of DHH students and provide flexibility of choice in meeting those needs [2].…”
Section: Introductionmentioning
confidence: 99%